Pengaruh Gaya Kepemimpinan Demokratis, Motivasi Intrinsik dan Iklim Organisasi terhadap Kinerja Karyawan Koperasi Simpan Pinjam di Kecamatan Rembang - Mohammad Aditiya Rama; Ming Ming Lukiarti (Universitas Nusantara PGRI Kediri, 2025)
The aim of this study is to explore and clarify how democratic leadership style, intrinsic motivation, and organizational climate impact employee performance in savings and loan cooperatives located in Rembang District. The research involved a sample of 111 marketing staff from 11 cooperatives, adhering to Law Number 25 of 1992 concerning Cooperatives. Data was gathered through questionnaires using a saturated sampling method. Multiple linear regression was implemented to analysis the data. Findings reveal that democratic leadership style has a minimal positive influence, while intrinsic motivation also shows only a minor positive impact; similarly, organizational climate presents a trivial positive effect on employee performance within the savings and loan cooperatives of Rembang District. With an Adjusted R Square value of 0.944, it indicates that 94.4% of the variation in employee performance can be explained by these three independent variables, leaving the remaining 5.6% subject to other unexamined influences not covered in this study.